Analisis Pengaruh Aspek Sikap, Persepsi, Dan Emosi Terhadap Penerapan Sistem Akuntansi Persediaan Pada PT. Mitra Usaha Flores - Merry Christanty; Wilhelmina Mitan; Yoseph Darius Purnama Rangga (Jurnal Mahasiswa Kreatif, 2023)
This study aims to determine the effect of attitudes, perceptions, and emotions on the implementation of the inventory accounting system that is run at PT. Flores Business Partners is a company that trades goods. The research population was all employees of PT. Flores Business Partners are 90 people. Meanwhile, the research sample was 55 respondents obtained from purposive sampling technique. Data collection in this research used primary data in the form of a questionnaire. The method of multiple linear regression analysis using SSPS 26. This study shows the results that the attitude aspect does not affect the application of the inventory accounting system. This is because the attitude of employees is classified as good so that they do the job according to the procedures set by the company. Meanwhile, aspects of perception and emotion influence the implementation of the accounting accounting system.